Acclimation of a low iron adapted Ostreococcus strain to iron limitation through cell biomass lowering - Botebol, Hugo; Lelandais, Gaelle; Six, Christophe; Lesuisse, Emmanuel; Meng, Arnaud; Bittner, Lucie; Lecrom, Stéphane; Sutak, Robert; Lozano, Jean-Claude; Schatt, Philippe; Vergé, Valérie; Blain, Stéphane; et al. (Scientific reports, 2017)
Iron is an essential micronutrient involved in many biological processes and is often limiting for primary production in large regions of the World Ocean. Metagenomic and physiological studies have identified clades or ecotypes of marine phytoplankton that are specialized in iron depleted ecological niches. Although less studied, eukaryotic picophytoplankton does contribute significantly to primary production and carbon transfer to higher trophic levels. In particular, metagenomic studies of the green picoalga Ostreococcus have revealed the occurrence of two main clades distributed along coast-offshore gradients, suggesting niche partitioning in different nutrient regimes. Here, we present a study of the response to iron limitation of four Ostreococcus strains isolated from contrasted environments. Whereas the strains isolated in nutrient-rich waters showed high iron requirements, the oceanic strains could cope with lower iron concentrations. The RCC802 strain, in particular, was able to maintain high growth rate at low iron levels. Together physiological and transcriptomic data indicate that the competitiveness of RCC802 under iron limitation is related to a lowering of iron needs though a reduction of the photosynthetic machinery and of protein content, rather than to cell size reduction. Our results overall suggest that iron is one of the factors driving the differentiation of physiologically specialized Ostreococcus strains in the ocean.
Keywords: aklimatizace; Gene Expression Profiling; Chlorophyta; železo; Trace Elements; stopové prvky; Acclimatization; Biomass; Iron; biomasa; stanovení celkové genové exprese